The accretion Disc evolution of the eclipsing cataclysmic variable EX Draconis - Harlaftis, E. T.; Steeghs, D.; Sokoloski, J.; Rutten, R. G. M.; Niarchos, P.; Gazeas, K.; Papadimitriou, C.; Manimanis, V. (5th Hellenic Astronomical Conference, 2001)
The dwarf nova EX Draconis shows deep and wide eclipses, in addition to its frequent outburst activity (every 2-3 weeks), which makes it the ideal target for monitoring a complete outburst cycle. We observed EX Draconis in BVI colours with the 1.2m telescope at Kryonerion Korinthias (Greece) between 1 July-20 August 2000 covering 3 outburst events (1-5 July, 20-30 July and 6-12 August). Here, we present a preliminary eclipse mapping study of the light curves obtained in August 2000.